The Use of Reverse Engineering Method in Designing Palm Fruit Collection Tools - Kurniawan, Fajar; Yola, Melfa; Nazaruddin, Nazaruddin; Harpito, Harpito; Umam, Muhammad Isnaini Hadiyul (Fakultas Teknik Universitas Tulang Bawang, 2026)
Product planning, design, and development are essential phases in manufacturing, starting from conceptualization and system design to production, testing, and ultimately delivering superior products that meet consumer demands. For instance, in the oil palm plantation industry, efficient tools play a vital role. Harvesting significantly affects the quality of oil palm yields, with losses often occurring due to loose fruit detachment from the Fresh Fruit Bunches (FFB), which fall to the ground. These loose fruits, known as